Pharmacognostical Evaluation of Seeds of Lepidium sativum Linn - Chauhan, Kshitij (International Journal of Pharmaceutical & Biological Archive, 2012)
Pharmacognostical Evaluation of Seeds of Lepidium sativum Linn